NURTURING CHILD PERSONALITY: THE CRUCIAL ROLE OF PARENTAL INFLUENCE - Hanifa, Dina Siti; Lestari, Triana (CV. TOTUS TUUS, 2024)
Parental influence on a child's personality development is paramount, as children are greatly shaped by their immediate environment, particularly the family. The family, being the smallest unit of society, serves as a fundamental arena for personality development. This paper explores the significance of parental roles in shaping a child's personality, emphasizing the impact of familial interactions and dynamics. Drawing from qualitative research methodology, this study delves into existing literature to analyze the multifaceted nature of parental influence on personality development. The findings underscore the crucial role of parents in fostering a nurturing environment conducive to healthy personality growth in children. Despite challenges such as busy schedules and technological distractions, parents must prioritize involvement in their children's lives, providing attention, affection, discipline, and guidance. By instilling values and fostering family harmony, parents play a pivotal role in shaping children into well-rounded individuals capable of thriving in society. Thus, understanding and actively engaging in parental roles are essential for facilitating positive personality development in children, ultimately contributing to their overall well-being and success in life.